The Function Theory and Its Application on Manuals of Economics - Gallardo, Ángel Rodríguez (HERMES - Journal of Language and Communication in Business, 2013)
In this paper, we analyse manuals of economics from the function point of view. Our proposal is focused on the classification and typology of manuals based on the communication purposes. In addition, we put forward and suggest certain improvements in the internal composition of the manuals based on a detailed analysis of their contents architecture and the rhetorical movements in which they are arranged. In general, we are suggesting that the new generation of manuals of economics, mostly multimodal ones, means and is going to be a significant step forward in the relationship between situations of use and learning processes.